2012
DOI: 10.4103/0974-8237.110121
|View full text |Cite
|
Sign up to set email alerts
|

Delayed anterior cervical plate dislodgement with pharyngeal wall perforation and oral extrusion of cervical plate screw after 8 years: A very rare complication

Abstract: We report a patient with congenital anomaly of cervical spine, who presented with clinical features suggestive of cervical compressive spondylotic myelopathy. He underwent C3 median corpectomy, graft placement, and stabilization from C2 to C4 vertebral bodies. Postoperative period was uneventful and he improved in his symptoms. Eight years later, he presented with a difficulty in swallowing and occasional regurgitation of feeds of 2 months duration and oral extrusion of screw while having food. On oral examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Delayed extrusions similar to our case have been described at 11 years in the gastrointestinal tract, Yamgoue Tchameni et al a pharyngoesophageal exposition 3 years after surgery, and Kapu et al after 8 years. In a review study, Newhouse et al found only 10 cases of delayed extrusion ranging from months to years.…”
Section: Discussionsupporting
confidence: 87%
“…Delayed extrusions similar to our case have been described at 11 years in the gastrointestinal tract, Yamgoue Tchameni et al a pharyngoesophageal exposition 3 years after surgery, and Kapu et al after 8 years. In a review study, Newhouse et al found only 10 cases of delayed extrusion ranging from months to years.…”
Section: Discussionsupporting
confidence: 87%
“…Secondly, ACP-induced compression to adjacent tissues may lead to esophageal and pharyngeal injury, dysphagia, and adjacent-level degeneration [912]. Furthermore, ACP or screw failure severely injures peripheral tissue, leading to serious consequences, even death [13,14]. These problems of ACP need to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical management of hardware migration is variable based on problem severity, patient's general condition, and the presence/risks of complications. 23 A surgical revision is not necessary for every patient. Conservative management of hardware migration is advised with no dislodged plate, if the patient is asymptomatic with no evidence of oesophageal perforation.…”
Section: Discussionmentioning
confidence: 99%